Precise determination of the B0s-B¯0s oscillation frequency - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich; Vagner A. R. Aleksandr Rudolfovich (2022, 2022)
Title screen